2022
DOI: 10.1002/pul2.12165
|View full text |Cite
|
Sign up to set email alerts
|

Commercial human pulmonary artery endothelial cells have in‐vitro behavior that varies by sex

Abstract: It is unknown whether biological sex influences phenotypes of commercially available human pulmonary artery endothelial cells (HPAECs). Ten lots of commercial HPAECs were used (Lonza Biologics; PromoCell). Five (50%) were confirmed to be genotypically male ( SRY +) and five (50%) were confirmed to be female ( SRY −). Experiments were conducted between passages five and eight. HPAEC phenotype was confirmed with a panel of cell expression markers. Standard assays for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 32 publications
2
6
0
Order By: Relevance
“…These data indicate that varying degrees of sex and gender - correlated gene expression exist across cancer types and that a predominant shared pattern between multiple cancers involves skewed gene expression in cell cycle regulation versus inflammation/immunity pathways. This validates the TI approach as these pathways are known to be strongly sex and gender-biased in action [ 11 14 ]. The replication of these polarization patterns across cancer types provides a measure of cross-validation for the approach.…”
Section: Resultssupporting
confidence: 59%
See 1 more Smart Citation
“…These data indicate that varying degrees of sex and gender - correlated gene expression exist across cancer types and that a predominant shared pattern between multiple cancers involves skewed gene expression in cell cycle regulation versus inflammation/immunity pathways. This validates the TI approach as these pathways are known to be strongly sex and gender-biased in action [ 11 14 ]. The replication of these polarization patterns across cancer types provides a measure of cross-validation for the approach.…”
Section: Resultssupporting
confidence: 59%
“…An accompanying analysis of survival data from 3.7 million cases in the Surveillance, Epidemiology, and End Results (SEER) database, representing approximately 28% of the cancer population, confirmed that mortality rates are higher for males compared to females [ 2 ]. These clinically important sex and gender differences are concordant with described sex differences in cell biology including response to genotoxic stress [ 3 , 4 ], DNA repair [ 5 , 6 ], mutational burden and oncogenic mechanisms [ 7 , 8 ], metabolism [ 9 , 10 ], and cell cycle regulation [ 11 13 ], as well as in systems biology including: immunity [ 14 ], metabolism [ 15 , 16 ], tissue repair [ 17 , 18 ], and longevity [ 19 , 20 ]. This suggests that therapies for all cancer patients may be advanced by a realistic translation of sex and gender differences into clinical practice.…”
Section: Introductionsupporting
confidence: 55%
“…An accompanying analysis of survival data from 3.7 million cases in the SEER database, representing approximately 28% of the cancer population, confirmed that mortality rates are higher for males compared to females [2]. These clinically important sex differences are concordant with described sex differences in cell biology including, response to genotoxic stress [3,4], DNA repair [5,6], mutational burden [7,8], metabolism [9,10], and cell cycle regulation [11][12][13], as well as in systems biology including: immunity [14], metabolism [15,16], tissue repair [17,18], and longevity [19,20]. This suggests that therapies for all cancer patients may be advanced by a realistic translation of sex differences into clinical practice.…”
Section: Introductionmentioning
confidence: 68%
“…The most common polarizations occur around male -cell cycle regulation and female -inflammation/immunity in both adult and pediatric cancers. This serves as validation for this approach as both mechanisms are already known to exhibit male-and female-biased action under normal conditions [11][12][13][14]. As both pathways are targetable with available therapeutics [27,28], it is interesting to consider how the TSI approach might inform stratification for treatment.…”
Section: Discussionmentioning
confidence: 99%
“…An accompanying analysis of survival data from 3.7 million cases in the Surveillance, Epidemiology, and End Results (SEER) database, representing approximately 28% of the cancer population, confirmed that mortality rates are higher for males compared to females [2]. These clinically important sex differences are concordant with described sex differences in cell biology including response to genotoxic stress [3,4], DNA repair [5,6], mutational burden and oncogenic mechanisms [7,8], metabolism [9,10], and cell cycle regulation [11][12][13], as well as in systems biology including: immunity [14], metabolism [15,16], tissue repair [17,18], and longevity [19,20]. This suggests that therapies for all cancer patients may be advanced by a realistic translation of sex differences into clinical practice.…”
Section: Introductionmentioning
confidence: 69%